Understanding the meanings of male partner support in the adherence to therapy among HIV-positive women: a gender analysis - Isotta Triulzi; Claire Somerville; Salimu Sangwani; Ilaria Palla; Stefano Orlando; Hawa Sangare Mamary; Fausto Ciccacci; Maria Cristina Marazzi; Giuseppe Turchetti (Taylor & Francis Group, 2022)
Background Previous literature reports that low male partner support is a barrier to women's adherence and retention in HIV care programs. Objective This qualitative study explored the relationships between partners to understand what is meant by male partner support in adherence of HIV-positive women in four healthcare facilities in Southern Malawi. Methods We conducted 8 semi-structured focus group discussions (FGDs) with 73 participants (40 men and 33 women) and 10 in-depth interviews (IDIs) between August 2018 to December 2019. Participants were HIV-positive patients, healthcare workers (HCWs), expert patients (EPs), and couples attending the clinic. All data were digitally recorded, transcribed verbatim, and analysed using a gender-responsive grounded theory approach. Results This study confirms previous literature, which suggests male partner support is expressed by providing access to transport to the clinic and accompaniment to appointments. However, we found that men can also control access to resources and decision-making. Support is more complex than previous literature reported and, in some cases, gender norms significantly limit women's capacity to engage in care independently of male support since women need male partner permission to access the resources to attend clinics. Conclusions This paper suggests that restrictive male-partner gender norms limit women's power to engage in care. Most importantly, the gender analysis reveals that what previous literature describes as male partner support can sometimes hide male partner control in permitting access to resources to attend health facilities. For this reason, policies enhancing male support should consider the gender power relationship between partners to avoid reinforcing gender inequality.